Prevalence of malocclusion among children of the Kingdom of Saudi Arabia – A systematic review and meta-analysis - Raghu Devanna; Nayef H. Felemban; Yousef Althomali; Prashant M. Battepati; Ahmed Ali Alfawzan; Puneet Gupta (Saudi Dental Journal)
Objective: Systematic review and meta-analysis are of a great tool in assessment of malocclusion, which is major public health concern. This study aims to explore the prevalence of malocclusion among the children of the Kingdom of Saudi Arabia through a meta-analysis and systematic review. Materials and methods: Registered with PROSPERO as CRD42020198427, an authentic and global scale database search using relevant MeSH (Medical Subject Headings) terms was performed. Literature search and articles screening done following PRISMA guidelines.For the dichotomous variables, 95% confidence intervals (CIs) were set for statistical data analysis. The heterogeneity index between the studies was determined using indices Tau2, Chi2, df and I2 and Test for overall effect as Z. Results: A total of 7930 candidates were reported to have either one of the three malocclusions. Prevalence of Class I, Class II and Class III Malocclusions were found to be 66.51%, 17.70%, 15.79% respectively. Among the small subsample of these candidates, male children with Class I, Class II and Class III Malocclusion were 43.80%, 12.27% and 7.40% respectively whereas female children were 22.07%, 10.93 %, 3.52 % respectively. Conclusions: According to the 26 studies included in the systematic review, there were 72% of the candidates with malocclusion in Saudi Arabia. Prevalence of Class I, Class II and Class III malocclusion were 66.51%, 17.70%, and 15.79% respectively. In both male and female participants, the prevalence of Class I was the highest followed by class II and III malocclusion.